Techno-scientific practices an informational approach - Russo, Federica 1978- (Rowman & Littlefield, 2022)
"This book looks at the practice of science and the role of technologies and instruments in the process of knowledge production by building bridges between the philosophy of science, philosophy of technology, and science and technology studies"--